Phytocoenotic assessment of herbaceous plant communities in the organic sweet cherry orchard - Gerasko, Tetyana; Герасько, Тетяна Володимирівна; Tymoshchuk, Tetiana; Moisiienko, Vira; Hrytsiuk, Natalia; Alekseeva, Tetiana (Ukraine, Zhytomyr, 2024)
EN: Biodiversity loss is one on global environmental issues facing humanity. Intensive use of natural resources has led to degradation of landscapes and reduction of the species diversity of plant communities. Therefore, finding natural solutions to overcome these challenges is an urgent issue. The purpose of the study was to investigate the dynamics of floral composition and coenotic structure of herbaceous plant communities in an organic cherry orchard for the sustainable functioning of theagricultural landscape. The dynamics of the coenotic composition of natural grasses of vegetation cover in the organic cherry orchard was studied during 2013-2020 in the arid conditions of the Southern Steppe of Ukraine on low-humus sandy loam soils. Morphological, ecological, and geographical methods were used to investigate the species diversity of flora in an organic garden. The composition of herbaceous plant communities was estimated using conbentional geobotanic description methods. The results of the study of the species composition and coenotic structure of plant communities of grass cover in an organic sweet cherry orchard are presented. Grassing of the garden with natural grasses has led to the enrichment of agricultural landscapes with useful species that are important components of sustainable agricultural systems and can perform ecological services. Colonisation of the grass cover by invasive and quarantine species was not observed due to natural processes of demutation succession and the use of moderate four-fold mowing of plants during the growing season (to a height of 15-20 cm). As part of herbal plant communities in the 8th year of research, all species were useful, had medicinal properties, and served as a food base. The natural grasses in an organic sweet cherry orchard are a resource of biomass and biodiversity. Phytocoenotic analysis of the grass cover in the organic cherry orchard will allow substantiating and proposing principles for predicting the development of plant communities to optimise their structure, improve quality, and maintain biodiversity.
Фітоценотична оцінка травʼяних рослинних угруповань органічного саду черешні
Keywords: species composition; biodiversity; environmental services; grass cover; coenomorphs; secondary succession; natural restoration of agroecosystems; видовий склад; біорізноманіття; екологічні послуги; трав’яний покрив; ценоморфи; вторинна сукцесія; природне відновлення агроекосистем